Analysis of the models for life cycle assessment of the building and building products - Taygun, Goekce Tuna; Balanli, Ayse (GH ASACHI TECHNICAL UNIV IASI, 2007)
The environment is the relations in life and all settings life is consist of A building is an artificial environment designed and built to meet the users' needs. These needs are fulfilled with the properties of building products that form the building. Building and building products are directly or indirectly in interaction with the environment during their life cycle process. There are some models like 'LEED', 'Athena', 'BEES', 'BRE', 'Analytica', 'Pre', 'GaBi', 'TEAM', 'GB Tool', 'Woolley', 'Curwell and March' developed by various corporations to assess environmental impacts of building or building products. In this study, these models are analyzed for; Definition of the models, Definition of the life cycle processes of the models, Determination of the environmental impact criterias of the models. A Life Cycle Assessment (LCA) model including all of 'cause, process of effect, effect and result' should be designed in order to prevent negative environmental impacts of building and building products. The aims of the model for LCA of building and/or building products are; to make the understanding and practicing of model easy and correct for its users to evaluate impacts of building and building products on the environment during all life cycle processes.
Keywords: environment; LCA; life cycle processes of building and building products; life cycle assessment models; ENVIRONMENTAL-IMPACT; Environmental Sciences & Ecology